2017
DOI: 10.21837/pmjournal.v15.i6.233
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of the Existence of Biomimicry Life’s Principles in Green Building Index Malaysia

Abstract: Concerns about climate change and global warming have led many countries to initiate energy rating systems in the planning and development of the built environment. Although useful and novel, this paper contends that these ratings are only remedying and alleviating whatever negative impacts that development creates. Energy ratings are seemingly lacking in attempts to integrate and enhance the physical development of the natural environment. Instead, biomimicry is adiscipline that explores nature and tries to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…To provide sustainable solutions, it is also described as imitating the functional foundation of biological forms, processes, and systems. Therefore, the guiding principle of biomimicry is proposed to be a paradigm shift of imaginative and problem-based learning required for education toward sustainability [6]. For example, Frank Lloyd Wright used mushroom structural principles to create the interior pillars for Johnson Wax's executive offices in Racine, Wisconsin, between 1936 and 1939, as illustrated in Figure (2), and Guggenheim Museum spiral ramp idea was inspired by seashells 1943 [7], as illustrated in Figure By observing how nature resolves issues that we now face, biomimicry design can be used to explore and extract suitable answers and new paths for our built environments.…”
Section: Figure (1) Theories Of Biomimicrymentioning
confidence: 99%
See 1 more Smart Citation
“…To provide sustainable solutions, it is also described as imitating the functional foundation of biological forms, processes, and systems. Therefore, the guiding principle of biomimicry is proposed to be a paradigm shift of imaginative and problem-based learning required for education toward sustainability [6]. For example, Frank Lloyd Wright used mushroom structural principles to create the interior pillars for Johnson Wax's executive offices in Racine, Wisconsin, between 1936 and 1939, as illustrated in Figure (2), and Guggenheim Museum spiral ramp idea was inspired by seashells 1943 [7], as illustrated in Figure By observing how nature resolves issues that we now face, biomimicry design can be used to explore and extract suitable answers and new paths for our built environments.…”
Section: Figure (1) Theories Of Biomimicrymentioning
confidence: 99%
“…In nature, the elephant can move its trunk in any direction. The robotic arm that was constructed at Rice university in the U.S simulates the elephant trunk design, as illustrated in Figure (6). And, in biology influence design approach [13], When biological information affects human design, the collaborative design process initially depends on people being familiar with pertinent biological or ecological research rather than on difficulties with identified human design.…”
Section: Figure (5) Comparison Of Biomimicry Techniquesmentioning
confidence: 99%